Poverty and Inequality Maps in Rural Vietnam: An Application of Small Area Estimation - Nguyen, Viet Cuong (2012)
The objective of the present paper is to estimate poverty and inequality for rural Vietnam at different levels of aggregation by combining the Vietnam Household Living Standard Survey from 2006 and the Rural Agriculture and Fishery Census from the same year. Using the small area estimation method, estimates at the regional, provincial and district level are produced, and both expenditure and income based measures are considered. It is found that all provinces across the country have experienced a noticeable reduction in rural poverty during the period 1999-2006. Some of the largest reductions in poverty are observed for provinces with poverty rates close to the national average. The poorest provinces are experiencing reductions in poverty, albeit at a more modest pace. Provinces and districts with a larger poverty reduction in the period 1999-2006 tended to have a lower level of inequality in 2006. Results based on expenditure poverty estimates are found to be very similar to those based on income poverty estimates.